As revoluções guiadas por mulheres na periferia do mundo muçulmano: Curdas e Saarauis 2022-2023 - Oliveira, Élica Libia Osório Perez de (Universidade Federal do Tocantins, 2024)
This work falls within the field of Women's History and aims to contribute to the history of women in the Global South. It proposes to comparatively analyze the speeches written by women from the Women's Defense Units(YPJ) and the National Union of Saharawi Women(UNMS) between 2022 and 2023 published on websites created by them, as well as their contributions to the struggles for self-determination of their people. Although these women are geographically separated by different continents, they face similar historical situations since the end of the 19th century and, from the 1970s onwards, even more similar situations, when they organized themselves politically. The research also shows us how the websites used are used as a new space for struggle and discursive ascension. This work adopts the Comparative History method theorized by Marc Bloch, by analyzing the speeches of these groups of women regarding Human Rights violations, using sources that are understood as new forms of communication.